# describe how to change the equation f(x0=x^2+4x-2, in order to reflect the function oer the y-axis. Also how to reflect it over x axis.

### 1 Answer | Add Yours

To reflect over the x axis, you would consider "instead of going up 4, go down 4", or "instead of y = 4, y = -4". That means, we would need to multiply the entire function (or y) by -1. So, for the reflection over the x axis:

f(x)=x^2+4x-2 ---> f(x) = (-1)(x^2+4x-2)

For reflection over the y axis, you would consider "instead of moving right, move left", or "instead of x = 4, x = -4". Therefore, we would multiply the x by -1. So, we would have:

f(x)=x^2+4x-2 ---> f(x) = (-x)^2+4(-x)-2